Epidemiology of poultry parasitism in village breeding in Niamey area (Niger) - Tager-Kagan, Pierre; Tibayrenc, Robert; Garba, Djibo (Revue d’élevage et de médecine vétérinaire des pays tropicaux, 1992)
An inventory of poultry parasitism in hens and Guinea fowls in Village breeding was conducted from May 1985 to April 1987 in the Niamey department. About 1,200 post-mortem examinations and haematological tests, as well as 6,000 faecal egg counts were performed. The internal polyparasitism was observed in two thirds of the cases. Guinea fowls were more infected than chickens. Cestodiasis was frequent in both species. The omnipresent spirochaetosis made a potential danger for the improved flocks. Ectoparasitoses were mainly represented by argas and scaly-legs, which affected one chicken out of ten.